Integrasi Kemampuan TPACK untuk Penguatan Kompetensi Pedagogi Guru SD Muhammadiyah se-Kecamatan Moyudan Sleman - Mardati, Asih; Sukma, Hanum Hanifa; Saifudin, Muhamad Fakhrur (Universitas Muhammadiyah Surakarta, 2022)
Based on the results of interviews conducted with teachers at SD Muhammadiyah Moyudan, it is known that there are obstacles in the implementation of online learning, including difficulties in providing learning so that two-way interaction does not occur, developing IT-based teaching materials, developing online learning evaluations, and teacher limitations. in using online applications and platforms. Therefore, there is a need for self-development for elementary school teachers in improving the ability of Technological Pedagogical Content Knowledge (TPACK). The purpose of this service is so that teachers can create and develop teaching materials with Kinemaster and evaluate learning using Google Form and Kahoot. This activity is carried out with a limited number of direct mentoring methods and integrated practice while still complying with the health protocol. The training implementation technique is carried out by demonstration, practice, discussion, mentoring. At the initial stage, it was done by demonstrating the introduction of various applications that can be used in online learning. Furthermore, the direct practice of making teaching materials and evaluation of online learning is carried out. The results of this activity are being able to develop TPACK-based learning tools, including the preparation of teaching materials using Kinemaster, Google forms, and Kahoot. The achievement of the results of this activity is 87.5% based on the results of the evaluation of the achievement of activities.